Measuring the Level of Creative Abilities of Future Physical Education Teachers and Trainers - نيوف, غيداء (Latakia University Journal -Medical Sciences Series, 2020)
This research presents the results of diagnostics of the level of personal creativity and creative possibilities for the students of Physical Education who will become teachers in the future and who are required this kind of potential required by the characteristics of the development of school education modern. The importance of research to develop the creative potential of the students applying to study in the Faculty of physical education and sports specialization in pedagogical education, first and foremost. As a result, a sample was selected from first-year students who attended "education". We have conducted research to diagnose the creative potential of students and potential physical (development of physical qualities). Results of the study showed that the level of this potential in the first-year students in the Faculty of physical education and sports competence "pedagogical education" is very low, compared with the level of physical abilities. Given that the material of physical education and sport is a fertile field for the implementation of creative abilities and affects the structural organization of the process education for teachers, therefore there is a need to provide this process to the software of appropriate and systematic preparation of programs for college students working on the development of creative thinking they have.